Echoing The Religious Moderation Through The Shared Christian Praxis Method - Berdame, Jekson; Wagiu, Meily Meiny; Mahardhika, Satria (Institut Agama Kristen Negeri Manado, 2024)
This research aims to give an offer regarding the strengthening of religious moderation concept through the Christian approach: Shared Christian Praxis. Departing from this current urgency where the religious freedom in Indonesia is a freshly happening issue, meanwhile there are still religious freedom offense around. By seeing that Indonesia has a characteristic which is pluralism, thus deemed necessary to embed the concept of religious moderation. This research has been done by using the qualitative method with literature study. Based on the applied content analysis, this SCP method could be the alternative way in terms of embedding and strengthening the moderation religious attitude, which can be crystallized in Christian educational environment, as well as in church. The result of this research is to fill the gap which in its praxis, moderation had been done in mainstream way.